The use of three-dimensional models in outsourcing academic activities for the presentation of civil engineering: an experience report (Research, Society and Development, 2023)
Engineering has a relevant theoretical and practical role in the social context. However, as far as the training of new professionals is concerned, the insufficiency and high dropout rates of engineering courses in Brazil, especially Civil Engineering, have been noted. In view of these factors, several studies and projects have arisen in order to provide opportunities for actions that minimize the consequences generated by the problem. This is the case of this work, which is the result of an extension project entitled "DespertEng: Awakening to Civil Engineering". This study is an experience report of the extension action of the DespertEng project, which aims to present didactic subsidies for actions to combat the civil engineering evasion process of the IFPB - Campus Patos. The actions occurred in four public institutions that are partners of the project, namely: ECIT Francisco De Sa Cavalcante (Paulista - PB); ECIT Sebastião Guedes da Silva (Teixeira - PB); ECIT Lynaldo Cavalcanti de Albuquerque (Patos - PB); Maria de Lourdes Meira (São José do Bonfim - PB). The results of the extension actions pointed out that strategies to strengthen the permanence process of the engineering courses and eventual student incentives would be focused on didactic actions and direct interconnection of the students with the course. Thus, at the end of the project activities, a large number of students were reached by the extension actions and it was evident that practical activities of interconnection of professions with future freshmen bring the professional choice closer to the demands of the course.